2018
DOI: 10.18633/biotecnia.v20i2.600
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Global and Analytical Training Methodologies for the Development of Technical Fundamentals Skills During Soccer Initiation Training on 8-9 and 10-11 Years Old Children

Abstract: Previous studies focused on the comparison of soccer teaching methodologies in sports initiation have not obtained conclusive results about the best methodology. Therefore, the main objective of this study was to compare the effect of global and analytical training-learning methodologies on some technical fundamental skills in children of 8-9 and 10-11 years old in soccer initiation. The technical skills evaluated by the test battery of “The Soccer Star Challenge” were running with the ball, dribbling, heading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In the course of a pedagogical experiment it is shown that at the beginning of the study, based on the normative requirements, the speed and strength and coordination indicators of young football players were average and below average level of development, corresponded to the assessment "satisfactory" and revealed a low level of training. Experts attribute this to the problems of the educational and training process in childhood and adolescence and the lack to date of a unified methodological approach in this matter (perhaps this fact should not be considered a negative point) and points to the need for further research [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In the course of a pedagogical experiment it is shown that at the beginning of the study, based on the normative requirements, the speed and strength and coordination indicators of young football players were average and below average level of development, corresponded to the assessment "satisfactory" and revealed a low level of training. Experts attribute this to the problems of the educational and training process in childhood and adolescence and the lack to date of a unified methodological approach in this matter (perhaps this fact should not be considered a negative point) and points to the need for further research [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Barquero-Ruiz et al (2022) suggest that tactical training in introductory football, including team, small groups and individuals, favoured the understanding of the game and tactical learning. In other research (Bernal-Reyes et al, 2018) they evaluated fundamentals such as dribbling, ball handling and striking the ball with both feet and head. The results indicated that both groups improved in all technical fundamentals at the end of the training programme.…”
Section: Work On Technique and Tacticsmentioning
confidence: 99%
“…According to Bernal-Reyes et al (2018) studies focused on the comparison of football teaching methodologies in sport initiation have not obtained conclusive results on which is the appropriate methodology in football teaching. The results of these authors (Bernal-Reyes et al, 2018) suggest that both the analytical and the global method seem adequate to improve the individual football skills of children in sport initiation.…”
Section: Work On Basic Physical Qualitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct instruction due to the automation of the mechanical movements carried out causes that the actions they execute are not understood by the students, so they depend on the instructions of their coach [ 7 ]. Sports education from a traditional approach generates some drawbacks, among which monotony and standardization stand out, as well as lack of motivation or the little time dedicated to promoting decision making [ 5 ], limiting creative development by using direct instruction methodology.…”
Section: Introductionmentioning
confidence: 99%